Bond-slip relationship of rebar in lightweight aggregate concrete. (November 2022) - Yang, Xue; Wu, Tao; Liu, Xi; Liu, Yang
Highlights: The bond-slip behavior of rebar in lightweight aggregate concrete (LWAC) considering the effect of additional embedded bars was experimentally investigated. The bond strength of LWAC was better than that of NWC at a lower W/B ratio. The existence of embedded bars altered the bond strength and failure mode of pull-out specimens. A shear strut mechanism was proposed to illustrate the effect of embedded bars on the bond-slip behavior of the rebar in LWAC. An analytical bond stress-slip model was developed by incorporating the assumed mechanism. Abstract: This paper presents the bond-slip relationship of deformed rebar in lightweight aggregate concrete (LWAC) considering the effect of additional embedded bars around the centric bar. Twelve groups of specimens considering the amount of embedded rebar, deployments, rebar diameters, and concrete types were constructed. The test results indicate that the additional embedded bars alter the bond-slip relationship and failure modes, which the proposed strut mechanism between rebars can illustrate. Next, an analytical solution for bond strength was derived based on a proposed strut mechanism and the thick-walled theory. A modified bond stress-slip model was then developed for LWAC by incorporating the proposed bond-strength equations, which were found to give a good prediction of the experimental results.